PENGARUH BRAND IMAGE DAN ETIKA BISNIS TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK JIMS HONEY PEMALANG - Ulfakhatun Ulfakhatun; Wenti Ayu Sunarjo (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2023)
Increasing technological developments cause consumers to be selective in making purchasing decisions. The study aims to determine whether Brand Image and Business Ethics have a significant effect on Purchasing Decisions both partially and simultaneously. Case studies conducted on Jims Honey consumers in Pemalang. The data collection technique in this study used a questionnaire in the form of a google form and literature review. Of the total research population of 35 people who were also used as samples (Saturated Sample). The instrument test used is validity test, reliability test and classical assumption test while the analysis to test the hypothesis is multiple linear regression analysis, t test and F test. This study concluded that Brand Image has a positive and insignificant effect on purchasing decisions partially, Business Ethics has a significant positive effect on purchasing decisions partially, Brand Image and Business Ethics have a positive and significant effect on purchasing decisions simultaneously (together).